Discriminant validation of measures of job satisfaction, job involvement, and organizational commitment. - Brooke, Paul P.; Russell, Daniel W.; Price, James L. (Journal of Applied Psychology, 1988)
Discriminant validity of measures of job satisfaction, job involvement, and organizational commitment was empirically evaluated using data collected from a sample of 577 full-time employees of a 327-bed Veterans Administration Medical Center, The LISREL vi computer program was used to conduct a confirmatory factor analysis of items from measures of these three concepts and to evaluate relations between other job-related variables and the three attitudinal measures. Results of these analyses indicated that the measures of job satisfaction, job involvement, and organizational commitment assess empirically distinct concepts.